2014
DOI: 10.1021/cn500214k
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Mitigates SNO-PDI Induced Aggregation of Parkinsonian Biomarkers

Abstract: Nitrosative stress mediated S-nitrosylation (SNO) of protein disulfide isomerase (PDI), a housekeeping oxidoreductase, has been implicated in the pathogenesis of sporadic Parkinson's (PD) and Alzheimer's (AD) diseases. Previous cell line studies have indicated that SNO-PDI formation provokes synphilin-1 aggregation, the minor Parkinsonian biomarker protein. Yet no work exists investigating whether SNO-PDI induces α-synuclein aggregation, the major Lewy body constituent associated with Parkinson's pathogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 45 publications
(109 reference statements)
3
47
0
Order By: Relevance
“…With respect to numerous reports in antioxidant role of EA on neuodegeneration [47][48][49][50], we can confirm anti-oxidative profile of EA. The SOD enzyme produces substrate for GPx activity in the brain under stressful situations [51,52].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With respect to numerous reports in antioxidant role of EA on neuodegeneration [47][48][49][50], we can confirm anti-oxidative profile of EA. The SOD enzyme produces substrate for GPx activity in the brain under stressful situations [51,52].…”
Section: Discussionsupporting
confidence: 80%
“…However, the long-time study in reperfusion phase to show more specific role and perceive mechanism of EA effect should be designed in future studies. Several line of evidences consistently supports the claim that ellagic acid improves antioxidant enzymes and subsequently these enzymes might defend neuronal cells against produced free radicals in brain injuries [47,48,49]. Herein, we detected the two antioxidant enzymes (SOD and GPx) in the present or absence of ellagic acid in ischemic rats' tissues.…”
Section: Discussionsupporting
confidence: 77%
“…Pretreatment was done for five days before the surgery. The doses of used compounds were chosen on the basis of our previous studies [25,40,43,57] as well as literature data [12,13,22,26,29,33,49,58,59]. Using the allometric calculation [60,61], a rat dose of 50 mg/kg (weight of 275 g male Wistar rats) of each compound (e.g., EA, LA or Myrt) would correspond to a human dose (human equivalent dose, HED) of approximately 9.8 mg/kg, which is near the clinical dose of amantadine (60 kg middle body human weight).…”
Section: Animal Groups and Experimental Protocolsmentioning
confidence: 99%
“…Of particular interest for this study is the reported ability of EA to lower the rotenone-induced generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in PC12 cells [22] as well as its ability to exhibit a neuroprotective effect against oxidative damage in diabetic rats by suppressing oxidative stress [23]. From cognitive and behavioral points of view, EA prevents scopolamine-and diazepam-induced cognitive impairments [24,25] and may be of potential benefit in brain stroke by alleviating the oxidative stress characteristic for this condition [26].…”
Section: Introductionmentioning
confidence: 99%
“…Protein disulfide isomerase (PDI) is associated with neurodegenerative diseases . Aberrant modification of PDI by SNO of active cysteine residues has been reported to be correlated closely to neurodegeneration in Parkinson's and Alzheimer's diseases . Therefore, quantitation of CCPs in PDI is fundamentally important for understanding disease development.…”
Section: Resultsmentioning
confidence: 99%